Pole piece and related battery monomer, battery and electric device

CN119605009APending Publication Date: 2025-03-11CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380056582.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-01-13
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The active materials in the existing pole pieces have poor liquid absorbing performance, resulting in poor cycle performance of the battery cells and unable to meet the high requirements of battery applications in electronic devices.

Method used

The polymer is introduced into the active material layer of the pole piece and synthesized through emulsion polymerization, suspension polymerization or solution polymerization to form a uniform high wetting point, improve the liquid absorption rate of the active material layer, and through specific structural units and molecular weight design , enhance the affinity between the electrolyte and the polymer, form an in-situ gel, and improve the infiltration performance of the electrolyte into the active material layer.

Benefits of technology

It significantly improves the battery cell cycle performance of the pole piece, enhances the infiltration ability of the electrolyte into the active material layer, and improves the kinetic performance and stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119605009A_ABST
    Figure CN119605009A_ABST
Patent Text Reader

Abstract

The invention provides a pole piece, a battery monomer related to the pole piece, a battery and an electric device. The pole piece comprises a current collector and an active substance layer arranged on at least one surface of the current collector, the active substance layer comprises an active substance and a polymer, the active substance layer meets the formula (1) to the formula (3), the polymer serves as a constituent part of the active substance layer, uniform high infiltration points can be formed in the active substance layer, and therefore the performance of the pole piece is improved. The infiltration performance of the active material layer is uniformly improved, so that the liquid absorption speed of the whole active material layer is improved, and the cycle performance of the battery monomer is improved. Formula (1) and formula (2) v / lambda > 1.00 Formula (3) # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Electrode and its related battery cells, batteries and electrical devices Technical Field

[0001] The present application relates to the field of batteries, and in particular to a pole piece and its related battery cell, battery and electrical device. Background Art

[0002] Battery cells have the characteristics of high capacity and long life, and are therefore widely used in electronic devices such as mobile phones, laptops, electric vehicles, electric airplanes, electric boats, electric toy cars, electric toy boats, electric toy airplanes and power tools, etc.

[0003] As battery applications expand, the performance requirements for battery cells are becoming increasingly stringent. To improve the safety of battery cells, optimization and improvement of the electrode performance within the cells are common. However, the active materials in the electrode currently have poor liquid absorption properties, resulting in poor cycling performance when used in battery cells.

[0004] Summary of the Invention

[0005] The present application is made in view of the above-mentioned problems, and its purpose is to provide a pole piece and its related battery cell, battery and electrical device.

[0006] A first aspect of the present application provides a pole piece, comprising a current collector and an active material layer disposed on at least one surface of the current collector, wherein the active material layer comprises an active material and a polymer, and the active material layer satisfies:

[0007]

[0008]

[0009] v / λ>1.00 Formula (3),

[0010] In formula (1) to formula (3),

[0011] λ represents the porosity of the active material layer;

[0012] P1 represents the actual compacted density of the active material layer, and its unit is g / cm 3 ;

[0013] P2 represents the actual compacted density of the active material, and its unit is g / cm 3 ;

[0014] v represents the liquid absorption rate of the active material layer, and its unit is mg / s.

[0015] d represents the diameter of the capillary of the active material layer in the capillary test, in mm;

[0016] h represents the height of the liquid level in the capillary tube, in mm;

[0017] ρ represents the density of the electrolyte in the capillary test, and its unit is g / cm 3 ;

[0018] t represents the time for the electrolyte to be absorbed in the capillary, and its unit is s.

[0019] Therefore, the polymer of the present application is introduced during the preparation process of the active material layer, which can form uniform high wetting points inside the active material layer, uniformly improve the wetting performance of the active material layer, thereby improving the overall liquid absorption speed of the active material layer, and thus improving the cycle performance of the battery cell using the electrode.

[0020] In some embodiments, the active material includes a positive electrode active material, and the active material layer satisfies: 1.00<v / λ<4.00; optionally, 1.20≤v / λ≤3.80.

[0021] In some embodiments, the active material includes a positive electrode active material, and the polymer has a mass percentage of A% based on the mass of the active material layer, where 0.1 ≤ A ≤ 1.5. When the mass percentage of the polymer is within this range, the liquid absorption capacity of the positive electrode active material layer can be significantly improved.

[0022] In some embodiments, the active material includes a negative electrode active material, and the active material layer satisfies: 3.00<v / λ<50.00; optionally, 3.40≤v / λ≤30.00.

[0023] In some embodiments, the active material includes a negative electrode active material, and the polymer has a mass percentage of B% based on the mass of the active material layer, wherein 0.2 ≤ B ≤ 5.0. When the mass percentage of the polymer is within this range, the liquid absorption capacity of the negative electrode active material layer can be significantly improved.

[0024] In some embodiments, the crystallinity of the polymer measured by differential scanning calorimetry is X C %,0<X C ≤30; the melting temperature of the polymer is Tm, the unit is ℃, 0<Tm≤140.

[0025] Therefore, in the present application, since the polymer and the electrolyte in the battery cell have good affinity, the solvent in the electrolyte can quickly diffuse between the molecular chains of the polymer and be wrapped by the molecular chains, and can form an in-situ gel on the surface of the active material, thereby improving the wetting performance of the electrolyte on the active material layer, thereby improving the overall liquid absorption speed of the active material layer, and thus improving the cycle performance of the battery cell using the electrode.

[0026] In some embodiments, the glass transition temperature of the polymer is Tg, expressed in degrees Celsius, where -150 ≤ Tg ≤ 60. A relatively low glass transition temperature of the polymer results in greater segmental flexibility in the molecular chain, making it easier for adjacent molecular chains to be opened and for in-situ gel formation to occur. This improves the wettability of the active material layer with the electrolyte, thereby enhancing the cycling performance of the battery cell.

[0027] In some embodiments, the polymer comprises at least one of the structural units represented by formula (I) to the structural units represented by formula (III),

[0028]

[0029] In formula (I) and formula (II), R1, R2, R3 and R4 each independently include a hydrogen atom, a fluorine atom, a chlorine atom, a substituted or unsubstituted C1-C3 alkyl group, or a substituted or unsubstituted C1-C3 alkoxy group, and at least one of R1, R2, R3 and R4 includes a fluorine atom; when substituted, the substituent includes a fluorine atom; in formula (III), R5 includes a single bond, a substituted or unsubstituted C1-C3 alkyl group; when substituted, the substituent includes a fluorine atom; p is a positive integer selected from 1 to 3; n is a positive integer selected from 1000 to 30000.

[0030] Therefore, the polymer of the present application is a straight-chain linear structure or a short-chain branched structure. This type of structure has a low degree of entanglement, which is conducive to improving the flexibility of the molecular chain. The molecular chain can fully stretch in the electrolyte, thereby further improving the wetting performance of the electrolyte on the active substance.

[0031] In some embodiments, R1, R2, R3 and R4 each independently include a hydrogen atom, a fluorine atom, a chlorine atom, a substituted or unsubstituted C1-C2 alkyl group or a substituted or unsubstituted C1-C2 alkoxy group; further optionally, R1, R2, R3 and R4 each independently include a hydrogen atom, a fluorine atom, a chlorine atom, a methyl group, a fluoromethyl group, a methoxy group or a perfluoromethoxy group.

[0032] In some embodiments, the polymer includes at least one of the structural units represented by formula (I-1) to the structural units represented by formula (I-11),

[0033]

[0034] In some embodiments, the polymer includes at least one of the structural units represented by formula (II-1) to the structural units represented by formula (II-5),

[0035]

[0036]

[0037] In some embodiments, the polymer includes at least one of the structural units represented by formula (III-1) to the structural units represented by formula (III-3),

[0038]

[0039] In some embodiments, n is a positive integer selected from 5,000 to 20,000.

[0040] In some embodiments, the molecular weight of the polymer is 2×10 5 g / mol to 1.5×10 6 g / mol. When the molecular weight of the polymer is within the above range, it can ensure that the polymer exhibits a certain solubility in the electrolyte, while not being easily completely dissolved and dispersed by the electrolyte, which is conducive to regulating the distribution and dispersion of the polymer on the surface of the active material, and can make the electrolyte evenly infiltrate the active material layer, thereby improving the overall liquid absorption speed of the active material layer, and can improve the cycle performance of the battery cell using the electrode; and can further improve the flexibility between the molecular chains of the polymer, and the interaction force between the molecular chains is relatively weak, which is conducive to the solvent molecules in the electrolyte opening the molecular chains and entering between the molecular chains and being wrapped by the molecular chains, thereby facilitating the active ions to enter the active material through the solvent, achieving smooth and rapid migration of the active ions, and improving the dynamic performance of the battery cell.

[0041] A second aspect of the present application provides a battery cell, which includes a pole piece according to any embodiment of the first aspect of the present application.

[0042] A third aspect of the present application provides a battery, comprising the battery cell as described in the second aspect of the present application.

[0043] A fourth aspect of the present application provides an electrical device comprising the battery cell as described in the third aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following is a brief introduction to the drawings required for use in the embodiments of the present application. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on the drawings without creative work.

[0045] FIG1 is a schematic diagram of a battery cell according to an embodiment of the present application.

[0046] FIG. 2 is an exploded schematic diagram of an embodiment of the battery cell of FIG. 1 .

[0047] FIG3 is a schematic diagram of an embodiment of a battery module of the present application.

[0048] FIG4 is a schematic diagram of an embodiment of a battery pack of the present application.

[0049] FIG. 5 is an exploded schematic diagram of the embodiment of the battery pack shown in FIG. 4 .

[0050] FIG6 is a schematic diagram of an embodiment of an electric device including the battery cell of the present application as a power source.

[0051] The drawings are not necessarily drawn to scale.

[0052] The following are the descriptions of the reference numerals:

[0053] 1. Battery pack; 2. Upper box; 3. Lower box; 4. Battery module;

[0054] 5. Battery cell; 51. Housing; 52. Electrode assembly;

[0055] 53. Cover plate;

[0056] 6. Electrical equipment. DETAILED DESCRIPTION

[0057] The following detailed description specifically discloses the embodiments of the polymer, electrode, and related battery cells, batteries, and electrical devices of the present application. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there may be cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0058] " range " disclosed in the present application is limited in the form of lower limit and upper limit, and given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of special range. The scope limited in this way can be to include end value or not include end value, and can be arbitrarily combined, that is, any lower limit can form a range with any upper limit combination. For example, if the scope of 60-120 and 80-110 is listed for specific parameters, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range value 1 and 2 are listed, and if the maximum range value 3,4 and 5 are listed, then the following range can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In this application, unless otherwise specified, the numerical range " ab " represents the abbreviation of any real number combination between a and b, wherein a and b are all real numbers. For example, a numerical range of "0-5" indicates that all real numbers between "0-5" are listed herein, and "0-5" is simply an abbreviation for these numerical combinations. Furthermore, when a parameter is expressed as an integer ≥ 2, this is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0059] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution. Unless otherwise specified, all technical features and optional technical features of the present application can be combined with each other to form a new technical solution.

[0060] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, a method includes steps (a) and (b), which indicates that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, a method may further include step (c), which indicates that step (c) may be added to the method in any order, for example, the method may include steps (a), (b), and (c), or may include steps (a), (c), and (b), or may include steps (c), (a), and (b), etc.

[0061] Unless otherwise specified, the terms "include" and "comprising" used in this application may be open-ended or closed-ended. For example, "include" and "comprising" may mean that other components not listed may also be included or that only the listed components are included.

[0062] Unless otherwise specified, the term "or" is used in this application to be inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, the condition "A or B" is satisfied if any of the following conditions are met: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0063] In this application, the terms "plurality" and "multiple" refer to two or more.

[0064] The term "alkyl" encompasses both straight and branched chain alkyl groups. For example, the alkyl group may be a C1-C5 alkyl group, a C1-C4 alkyl group, a C1-C3 alkyl group, or a C1-C2 alkyl group. In some embodiments, the alkyl group includes a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, an isobutyl group, and the like. Additionally, the alkyl group may be optionally substituted. When substituted, the substituent includes a fluorine atom.

[0065] The term "alkoxy" refers to a group in which an alkyl group is connected to an oxygen atom by a single bond. For example, the alkoxy group can be a C1 to C5 alkoxy group, a C1 to C3 alkoxy group, or a C1 to C2 alkoxy group. In some embodiments, the alkoxy group can include a methoxy group, an ethoxy group, or a propoxy group. In addition, the alkoxy group can be optionally substituted.

[0066] The term "halogen atom" refers to a fluorine atom, a chlorine atom, a bromine atom or the like.

[0067] The term "hydrogen" refers to 1H (protium, H), 2H (deuterium, D), or 3H (tritium, T). In various embodiments, "hydrogen" may be 1H (protium, H).

[0068] A battery cell includes an electrode assembly and an electrolyte. The electrode assembly includes a positive electrode sheet, a negative electrode sheet, and a separator disposed between the positive electrode sheet and the negative electrode sheet. The electrode assembly has a gap-pore structure. The electrolyte infiltrates the electrode assembly. The driving force for infiltration is mainly capillary force, which is a spontaneous infiltration process. Due to the barrier of the current collector in the electrode sheet, the electrolyte infiltrates from the end face of the electrode assembly through the separator into the interior of the electrode assembly. Therefore, the interlayer gap of the electrode assembly plays a guiding role, and the separator plays a diversion role. The steps of electrolyte infiltration in the electrode assembly include: (1) the electrolyte is transferred in the gap between the electrode sheet and the separator under the action of capillary force; (2) the electrolyte preferentially infiltrates in the pores of the separator (the electrolyte infiltration rate in the separator is much greater than that in the active material layer of the electrode sheet); (3) the electrolyte diffuses through the separator to the surface of the positive electrode sheet and the negative electrode sheet on both sides and infiltrates into the pores of the active material layer.

[0069] The inventors discovered that a polymer is required as a binder in the active material layer to bond the active material to the surface of the current collector. Since the polymer needs to be immersed in the electrolyte for a long time, a polymer with high crystallinity is typically used to maintain good performance and maintain good bonding and support for the active material layer. However, the electrode plates using these polymers have poor affinity for the electrolyte and poor wettability, resulting in a slow diffusion rate of the electrolyte from the surface of the active material layer into the interior of the active material layer, poor liquid absorption by the active material, and thus deteriorating the cycling performance of the battery cells.

[0070] In view of this, the inventors have improved the materials in the active material layer, such as polymers, from the perspective of improving the liquid absorption rate of the active material layer, in order to increase the liquid absorption speed and thus improve the cycle performance of the battery cell.

[0071] Pole

[0072] In a first aspect, the present application provides an electrode sheet; the electrode sheet comprises a current collector and an active material layer disposed on at least one surface of the current collector, wherein the active material layer comprises an active material and a polymer. The electrode sheet may be a positive electrode sheet and / or a negative electrode sheet; accordingly, the positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer; and the negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer.

[0073] The pole piece can be made by coating a slurry on a current collector, drying it, and cold pressing it. Alternatively, the pole piece can be made from a battery cell. The battery cell is disassembled, and the pole piece soaked in electrolyte is removed from the battery cell. The pole piece soaked in electrolyte is placed under vacuum drying at 100°C for 12 hours to obtain the pole piece, which can be used for pole piece testing such as liquid absorption rate.

[0074] Polymers can be synthesized through emulsion polymerization, suspension polymerization, bulk polymerization, solution polymerization, and other methods. Alternatively, the polymer can be derived from a battery cell. The battery cell is disassembled, and the electrode, which is immersed in the electrolyte, is removed. The active material of the electrode is then peeled off from the current collector by external force to form a powder sample. This powder is then added to dimethyl carbonate (DMC) and stirred at 80°C for 8 hours at 500 rpm. After stirring, the mixture is allowed to stand at room temperature for 10 minutes. The supernatant is then dried at 80°C for 12 hours to obtain the polymer. The resulting polymer may contain a small amount of lithium salt, but this has little impact on infrared and precipitation value testing. To ensure the accuracy of the polymer, the lithium salt can be further separated by rinsing with DMC at room temperature.

[0075] The active material layer satisfies:

[0076]

[0077]

[0078] v / λ>1.00 Formula (3),

[0079] In formula (1) to formula (3),

[0080] λ represents the porosity of the active material layer;

[0081] P1 represents the actual compacted density of the active material layer, and its unit is g / cm 3 ;

[0082] P2 represents the actual compacted density of the active material, and its unit is g / cm 3 ;

[0083] v represents the liquid absorption rate of the active material layer, and its unit is mg / s.

[0084] d represents the diameter of the capillary of the active material layer in the capillary test, in mm;

[0085] h represents the height of the liquid level in the capillary tube, in mm;

[0086] ρ represents the density of the electrolyte in the capillary test, and its unit is g / cm 3 ;

[0087] t represents the time for the electrolyte to be absorbed in the capillary, and its unit is s.

[0088] In this application, the actual compaction density P1 refers to the ratio of the mass of the active material layer per unit area in the electrode to its thickness. The actual compaction density is determined by the force of the roller pressing after the electrode is coated, and the unit is g / cm 3 The specific test steps are to take a certain area S of the electrode, weigh the mass M of its active material layer, and measure the thickness D of the active material layer. The actual compaction density = M / (S×D).

[0089] In this application, the true compaction density P2 refers to the density of the active material itself in the active material layer. For example, the active material is a negative electrode active material such as graphite, and the density of graphite is 2.25 g / cm 3 The actual compacted density of the active material is 2.25 g / cm 3 .

[0090] Taking the positive electrode active material as an example, specifically, it refers to the mass of the unit "actual volume of solid material (excluding open and closed pores and pores between particles)" in a dense state. The true volume V is obtained by testing, and then the true compaction density is calculated according to P = m / V. The test can be carried out in accordance with GB / T24586-2009; specifically, the test steps are as follows:

[0091] 1) Pretreatment: Place a clean and dry sample cup on a balance, reset it to zero, add the powder sample to the cup, filling it to about 1 / 2 of the cup volume, and record the sample mass.

[0092] 2) Place the sample cup containing the sample in the true density tester, seal the test system, and introduce helium according to the program. By detecting the pressure of the gas in the sample chamber and expansion chamber, the true volume is calculated according to Bohr's law (PV=nRT), and thus the true compacted density is calculated.

[0093] Among them, the volume of the sample cup is: 3.5cm 3 ;Analytical gas: helium.

[0094] Formula (1) can be used to calculate the porosity λ of the active material layer through the actual compaction density and the true compaction density.

[0095] Specifically,

[0096] Where V1 represents the volume of the active material layer under mass m, and its unit is cm 3 ;

[0097] V2 represents the volume occupied by the active particles in the active material layer under mass m, and its unit is cm 3 ;

[0098] m represents the mass of the active material layer, and its unit is g.

[0099] Formula (2) can represent the speed at which a certain point of the electrode completely absorbs the liquid (e.g., electrolyte) in the capillary per unit time. In this application, a certain point of the electrode refers to an area of ​​the electrode with a certain area, and its area corresponds to the cross-sectional area of ​​the capillary.

[0100] In this application, the method for detecting the liquid absorption rate of the electrode comprises the following steps:

[0101] A predetermined amount of electrolyte is drawn by a capillary tube;

[0102] The capillary is brought into contact with the electrode, and the electrode to be tested absorbs the electrolyte in the capillary under capillary action;

[0103] After a predetermined time t, the liquid level h of the electrolyte absorbed in the capillary is recorded, and the amount of electrolyte absorbed is calculated based on the liquid level h and diameter d of the capillary and the density ρ of the electrolyte. The liquid absorption rate v of the electrode is quantitatively calculated based on the ratio of the absorbed amount and the predetermined time t.

[0104] Exemplarily, d takes a value of 0.2 to 1, for example, a value of 0.2; h takes a value of 3 to 5, for example, a value of 3.

[0105] The capillary tube has capillary channels that allow it to directly absorb electrolyte through capillary action, without the need for an external drive unit to provide suction power. This allows, on the one hand, more precise control of the amount of electrolyte absorbed through capillary action; on the other hand, because the electrode absorbs electrolyte through its own capillary action, the electrode only draws electrolyte from the capillary tube when the capillary tube contacts the electrode under test. When contact is broken, the electrolyte in the capillary tube stops flowing. Therefore, the amount of electrolyte absorbed in the capillary tube accurately reflects the amount of electrolyte absorbed by the electrode, further improving the accuracy of the test results and enabling quantitative calculation of the electrode's absorption rate.

[0106] Formula (3) represents the liquid absorption rate of the electrode under the porosity λ, which can be used to characterize the liquid absorption speed of the electrode.

[0107] The polymer of the present application is introduced during the preparation process of the active material layer, which can form uniform high wetting points inside the active material layer, uniformly improve the wetting performance of the active material layer, thereby increasing the overall liquid absorption speed of the active material layer, thereby improving the cycle performance of the battery cell using the electrode.

[0108] Optionally, 1.00<v / λ<50.00.

[0109] In some embodiments, the crystallinity of the polymer measured by differential scanning calorimetry is X C %,0<X C ≤30; the melting temperature of the polymer is Tm, the unit is ℃, 0<Tm≤140.

[0110] Crystallization refers to the process in which atoms, ions or molecules in a material are arranged in a certain spatial order to form an orderly structure. The conformation of the polymer in the crystallization is determined by both intramolecular and intermolecular factors. Intermolecular forces affect the packing density between molecular chains. C % is used to characterize the degree of crystallinity in the material, which can be measured by differential scanning calorimetry (DSC). Specifically, the test steps are: take 0.5g to 0.8g of sample, place the sample in a carrier crucible, and perform temperature raising and lowering treatment on the sample in a nitrogen atmosphere, heating the sample at a rate of 10℃ / min from an initial temperature 20℃ lower than the intrinsic Tg of the material to a cutoff temperature 20℃ higher than the intrinsic Tm of the material, and determine the actual glass transition temperature Tg and melting temperature Tm of the material based on the endothermic and exothermic peak or transition point of the material in the process.

[0111] Compared to the fluorinated polymers commonly used in secondary batteries in related technologies, which have relatively high crystallinity and melting temperatures, the polymers have good resistance to liquid electrolytes, thereby effectively providing long-term adhesion or rebound suppression effects on active materials during battery use. The above-mentioned polymers (fluorinated polymers) used in this application have relatively low crystallinity and melting temperatures, which make the molecular chains tend to be loose, the interaction forces between the molecular chains are small, and the flexibility of the chain segments can be exerted, and adjacent molecular chains can be easily opened.

[0112] Since the polymer and the electrolyte in the battery cell have good affinity, the solvent in the electrolyte can quickly diffuse between the molecular chains of the polymer and be wrapped by the molecular chains, forming an in-situ gel on the surface of the active material, thereby improving the wetting performance of the electrolyte on the active material layer, thereby improving the overall liquid absorption speed of the active material layer, and thus improving the cycle performance of the battery cell using the electrode.

[0113] For example, the crystallinity X of the polymer measured by differential scanning calorimetry is C % can be 5%, 10%, 15%, 20%, 25%, 30% or a range consisting of any two of the above values.

[0114] For example, the melting temperature of the polymer may be 10°C, 20°C, 50°C, 70°C, 90°C, 100°C, 120°C, 140°C, or a range consisting of any two of the foregoing values.

[0115] In some embodiments, the glass transition temperature of the polymer is Tg, which is expressed in ° C., and is -150≤Tg≤60.

[0116] The glass transition temperature is the temperature at which the polymer chain segments transition from freezing to movement. The glass transition temperature has a certain influence on the flexibility of the polymer molecular chain. The lower the glass transition temperature, the better the flexibility of the polymer molecular chain at room temperature. The higher the glass transition temperature, the worse the flexibility of the molecular chain at room temperature. The glass transition temperature can be measured by differential scanning calorimetry (DSC). The lower the glass transition temperature of the polymer, the more flexible the molecular chain segments are, the easier it is for adjacent molecular chains to be opened, and the easier it is to form an in-situ gel, thereby improving the wettability of the electrolyte to the active material layer, thereby improving the cycle performance of the battery cell. For example, the glass transition temperature of the fluorinated polymer can be -150°C, -140°C, -120°C, -100°C, -80°C, -60°C, -30°C, 0°C, 30°C, 60°C, or a range consisting of any two of the above values.

[0117] In some embodiments, the polymer comprises at least one of the structural units represented by formula (I) to the structural units represented by formula (III),

[0118]

[0119] In formula (I) and formula (II), R1, R2, R3 and R4 each independently include a hydrogen atom, a fluorine atom, a chlorine atom, a substituted or unsubstituted C1-C3 alkyl group or a substituted or unsubstituted C1-C3 alkoxy group, and at least one of R1, R2, R3 and R4 includes a fluorine atom; when substituted, the substituent includes a fluorine atom.

[0120] In formula (III), R5 includes a single bond, a substituted or unsubstituted C1-C3 alkyl group; when substituted, the substituent includes a fluorine atom. p is a positive integer selected from 1 to 3.

[0121] n is a positive integer selected from 1,000 to 30,000.

[0122] In some embodiments, R1, R2, R3 and R4 each independently include a hydrogen atom, a fluorine atom, a chlorine atom, a substituted or unsubstituted C1-C2 alkyl group, or a substituted or unsubstituted C1-C2 alkoxy group, and at least one of R1, R2, R3 and R4 includes a fluorine atom.

[0123] In some embodiments, R1, R2, R3 and R4 each independently include a hydrogen atom, a fluorine atom, a chlorine atom, a methyl group, a fluoromethyl group, a methoxy group or a perfluoromethoxy group.

[0124] In some embodiments, the polymer includes at least one of the structural units represented by formula (I-1) to the structural units represented by formula (I-11),

[0125]

[0126] Optionally, the polymer includes at least two of the structural units represented by formula (I-1) to the structural units represented by formula (I-11).

[0127] In some embodiments, the polymer includes at least one of the structural units represented by formula (II-1) to the structural units represented by formula (II-5),

[0128]

[0129]

[0130] In some embodiments, the polymer includes at least one of the structural units represented by formula (III-1) to the structural units represented by formula (III-3),

[0131]

[0132] Exemplarily, the polymer includes one or more of polyperfluoroethylene (PTFE), polyvinylidene fluoride (PVDF), perfluoroethylene propylene copolymer (FEP), perfluoroalkoxy polymer (PFA), perfluoropolyether (PFPE), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), polyvinylidene fluoride-trifluoroethylene copolymer (PVDF-TrFE) and perfluoro (1-butenyl vinyl ether) polymer (CYTOP for short).

[0133] Optionally, the polymer includes one or more of polyperfluoroethylene (PTFE), polyvinylidene fluoride (PVDF), perfluoroethylene propylene copolymer (FEP), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), and polyvinylidene fluoride-trifluoroethylene copolymer (PVDF-TrFE).

[0134] The above polymer may be derived from one or more of the following monomers: fluorocycloethane, vinyl fluoride, 1,2-difluoroethylene, vinylidene fluoride, trifluoroethylene, chlorotrifluoroethylene, tetrafluoroethylene, hexafluoropropylene, 3,3,3-trifluoropropylene, trifluoropropylene, tetrafluoropropylene and pentafluoropropylene. Alternatively, the above polymer may be derived from at least two of the following monomers: fluorocycloethane, vinyl fluoride, 1,2-difluoroethylene, vinylidene fluoride, trifluoroethylene, chlorotrifluoroethylene, tetrafluoroethylene, hexafluoropropylene, 3,3,3-trifluoropropylene, trifluoropropylene, tetrafluoropropylene and pentafluoropropylene.

[0135] The monomers used in the above-mentioned polymers are all short-chain monomers, which are conducive to the polymerization to form a straight-chain linear structure or a short-chain branched structure. This type of structure has a low degree of entanglement, which is conducive to improving the flexibility of the molecular chain. The molecular chain can fully stretch in the electrolyte, thereby further improving the wettability of the electrolyte to the active substance and improving the interfacial performance of the active substance.

[0136] The groups of the polymers of the present application can be detected by infrared spectrophotometry IR. Specifically, the polymers are tested using a Thermo Nicolet Nexus 670 attenuated total reflectance Fourier transform infrared spectrometer (FTIR-ATR), and then tested in accordance with the standard GB / T6040-2002. The test range is: ATR method 600-4000 cm -1 ; Repeatability: ±2cm -1 ; Resolution: better than 4cm -1 ; Transmission depth 0.2~0.6μm.

[0137] The structure of the polymer of the present application can be tested by nuclear magnetic resonance (NMR). Specifically, 1H NMR and 13C NMR are performed on a Varian Mercury Plus-400 NMR spectrometer at a test temperature of 20° C., TMS as an internal standard, CDCl 3 as a solvent, and a proton resonance frequency of 400 MHz.

[0138] In some embodiments, n is a positive integer selected from 5,000 to 20,000.

[0139] In some embodiments, the molecular weight of the polymer is 2×10 5 g / mol to 1.5×10 6 g / mol.

[0140] When the molecular weight of the polymer is within the above range, it can ensure that the polymer exhibits a certain solubility in the electrolyte, while not being easily completely dissolved and dispersed by the electrolyte, which is conducive to regulating the distribution and dispersion of the polymer on the surface of the active material, and can make the electrolyte evenly infiltrate the active material layer, thereby improving the overall liquid absorption speed of the active material layer, and can improve the cycle performance of the battery cell using the electrode; and can further improve the flexibility between the molecular chains of the polymer, and the interaction force between the molecular chains is relatively weak, which is conducive to the solvent molecules in the electrolyte opening the molecular chains and entering between the molecular chains and being wrapped by the molecular chains, thereby facilitating the active ions to enter the active material through the solvent, and realizing the smooth and rapid migration of the active ions. For example, the molecular weight of the polymer can be 2×10 5 g / mol, 5×10 5 g / mol, 8×10 5 g / mol, 1×10 6 g / mol, 1.5×10 6 g / mol or a range consisting of any two of the above values.

[0141] The molecular weight of a polymer is well known in the art and can be measured using equipment and methods commonly used in the art. Gel permeation chromatography (GPC) testing can be used. The specific testing steps are as follows: take an appropriate amount of the sample to be tested (the sample concentration is sufficient to ensure 8%-12% shading), add 20 ml of deionized water, and simultaneously operate externally for 5 minutes (53 KHz / 120 W) to ensure that the sample is completely dispersed. Then, the sample is measured in accordance with GB / T19077-2016 / ISO 13320:2009 standard.

[0142] Alternatively, a multi-angle laser light scattering (MALLS) instrument was used for testing. Specifically, a GPC coupled with a Dawn Heleos II multi-angle laser light scattering device, an Optilab T-rEX refractive index (RI) detector, and a Visco Star II viscometer (Wyatt Technology Corporation, USA) was used. Testing was conducted at 30°C, using tetrahydrofuran as the mobile phase at a flow rate of 1.0 ml / min. SEC-SAMLL data were processed using the commercial ASTRA6 software to obtain molecular weight parameters.

[0143] After further research, the inventors found that when the polymer also meets one or more of the following conditions, the cycle performance of the battery cell can be further improved.

[0144] In some embodiments, the polymer is added to a first solvent at a first temperature to form a polymer system; the polymer system is allowed to stand at the first temperature for 8 hours and then at a second temperature for ≥24 hours. After undergoing these two stages of standing, the polymer system partially or completely transforms in situ into a gel-like substance; the polymer system is then filtered through a 200-mesh filter to leave the first substance. The first temperature is greater than the second temperature. The mass of the polymer is n, in g; the mass of the first substance is m, in g. The polymer and the first substance satisfy the following conditions: 5 ≤ m / n ≤ 1000; alternatively, 10 ≤ m / n ≤ 1000; further alternatively, 10 ≤ m / n ≤ 50. Exemplarily, m / n can be 5, 10, 20, 25, 28, 30, 32, 35, 40, 50, 80, 100, 200, 500, 1000, or a range consisting of any two of these values.

[0145] Illustratively, based on the mass of the polymer system, the ratio of the mass content of the polymer to the mass content of the first solvent ranges from 1:100 to 1:10, for example, 3:50.

[0146] Exemplarily, the first solvent is the same as or similar to the solvent of the electrolyte, and the first solvent may include a carbonate solvent, for example, a carbonate solvent including a cyclic carbonate solvent and / or a linear carbonate solvent.

[0147] As examples of the cyclic carbonate solvent, the cyclic carbonate solvent includes one or more of ethylene carbonate EC, vinylene carbonate VC, fluoroethylene carbonate FEC, difluoroethylene carbonate DFEC, vinyl ethylene carbonate VEC, and dioctyl carbonate CC.

[0148] As examples of the linear carbonate solvent, the linear carbonate solvent includes one or more of dimethyl carbonate DMC, diethyl carbonate DEC, ethyl methyl carbonate EMC, diphenyl carbonate DPC, methyl allyl carbonate MAC, and polycarbonate VA.

[0149] Optionally, the first solvent may also contain a lithium salt and an electrolyte additive, such as lithium hexafluorophosphate, vinylene carbonate VC, fluorovinylene carbonate FEC, and the like.

[0150] In this application, m / n is also referred to as the precipitation value, which characterizes the ability of the polymer and solvent to transform into a gel-state substance.

[0151] The first substance mainly includes a gel-state substance formed by a polymer and a first solvent. In this type of gel-state substance, the molecular structure of the polymer basically does not change.

[0152] In some embodiments, the first substance is dried at 80° C. for 12 hours to remove the first solvent in the first substance. Detection by infrared spectrophotometry IR or nuclear magnetic resonance NMR testing shows that the main component of the first substance after drying is the polymer described above.

[0153] In the present application, the glass transition temperature of the polymer is ≤ the first temperature ≤ the melting temperature of the polymer, and the first temperature is the normal use temperature of the battery cell.

[0154] The first temperature is greater than the second temperature. The first temperature and the second temperature can be set to the safe operating temperature range of the battery cell. For example, the first temperature can be 60°C to 80°C, such as 70°C, and the second temperature can be -30°C to 30°C, such as 25°C. That is, the first temperature is the higher operating temperature of the battery cell, and the second temperature is approximately room temperature or low temperature.

[0155] By increasing the temperature, this application can achieve stretching of the polymer molecular chains within the safe operating temperature range of the battery cell, promoting mutual attraction and physical bonding between the polymer molecular chains and the solvent, thereby improving liquid absorption capacity. At room temperature, the activity of the polymer molecular segments is reduced, maintaining adhesion to the surface of the active material and locking the electrolyte in the spatial environment of the polymer, forming a state similar to in-situ gel, improving liquid retention and cycle performance.

[0156] [Positive electrode]

[0157] The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer includes a positive electrode active material and a polymer. In the present application, the polymer includes the polymer described above.

[0158] For example, the positive electrode current collector has two surfaces facing each other in its thickness direction, and the positive electrode active material layer is disposed on either or both of the two facing surfaces of the positive electrode current collector.

[0159] In some embodiments, 1.00 < v / λ < 4.00; alternatively, 1.20 ≤ v / λ ≤ 3.80; further alternatively, 1.4 ≤ v / λ ≤ 3.6. For example, v / λ can be 1.20, 1.40, 1.80, 2.00, 2.50, 3.00, 3.50, 3.60, 3.80, 3.90, or a range consisting of any two of the above values.

[0160] In some embodiments, based on the mass of the positive electrode active material layer, the mass percentage of the polymer is A%, wherein 0.1≤A≤1.5.

[0161] When the polymer content by weight is within the above range, the liquid absorption capacity of the positive electrode active material layer can be significantly improved. For example, the polymer content by weight A% can be 0.1%, 0.2%, 0.5%, 0.8%, 1.0%, 1.2%, 1.5%, or a range consisting of any two of the above values.

[0162] The positive electrode active material layer includes a positive electrode active material, and the positive electrode active material can be a positive electrode active material for a battery cell known in the art. As an example, the positive electrode active material can include at least one of the following materials: a layered positive electrode active material (such as ternary, lithium nickelate / sodium, lithium cobaltate / sodium, lithium manganate / sodium, lithium-rich / sodium layered, and rock salt phase layered materials), an olivine-type phosphate active material, and a spinel-structured positive electrode active material (such as spinel lithium manganate, spinel lithium nickel manganate, lithium-rich spinel lithium manganate, and lithium nickel manganate, etc.).

[0163] For example, the general formula of the layered positive electrode active material is: Li x A y Ni a Co b Mn c M (1-a-b-c) Y z, wherein 0≤x≤2.1, 0≤y≤2.1, and 0.9≤x+y≤2.1; 0≤a≤1, 0≤b≤1, 0≤c≤1, and 0.1≤a+b+c≤1; 1.8≤z≤3.5; A is selected from one or more of Na, K, and Mg; M is selected from one or more of B, Mg, Al, Si, P, S, Ca, Sc, Ti, V, Cr, Fe, Cu, Zn, Sr, Y, Zr, Nb, Mo, Cd, Sn, Sb, Te, Ba, Ta, W, Yb, La, and Ce; Y is selected from one or more of O and F. Optionally, y=0. Specifically, the layered structure positive electrode active material may include lithium cobalt oxide LCO, lithium nickel oxide LNO, lithium manganese oxide LMO, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2(NCM333),LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM811) and LiNi 0.5 Co 0.2 Mn 0.3 One or more of O2 (NCM523).

[0164] For example, the general formula of the olivine phosphate active material is: Li x A y Me a M b P 1-c X c Y z , wherein, 0≤x≤1.3, 0≤y≤1.3, and 0.9≤x+y≤1.3; 0.9≤a≤1.5, 0≤b≤0.5, and 0.9≤a+b≤1.5; 0≤c≤0.5; 3≤z≤5; A is selected from one or more of Na, K, and Mg; Me is selected from one or more of Mn, Fe, Co, and Ni; M is selected from one or more of B, Mg, Al, Si, P, S, Ca, Sc, Ti, V, Cr, Cu, Zn, Sr, Y, Zr, Nb, Mo, Cd, Sn, Sb, Te, Ba, Ta, W, Yb, La, and Ce; X is selected from one or more of S, Si, Cl, B, C, and N; and Y is selected from one or more of O and F. Specifically, the olivine-type phosphate active material includes one or more of LiFePO4, LiMnPO4, LiNiPO4, and LiCoPO4.

[0165] For example, the general formula of the positive electrode active material of the spinel structure is: Li x A y Mn a M 2-a Y z, wherein 0≤x≤2, 0≤y≤1, and 0.9≤x+y≤2; 0.5≤a≤2; 3≤z≤5; A is selected from one or more of Na, K, and Mg; M is selected from one or more of Ni, Co, B, Mg, Al, Si, P, S, Ca, Sc, Ti, V, Cr, Fe, Cu, Zn, Sr, Y, Zr, Nb, Mo, Cd, Sn, Sb, Te, Ba, Ta, W, Yb, La, and Ce; and Y is selected from one or more of O and F. Specifically, the positive active materials of the spinel structure include LiMn2O4, LiNi 0.5 Mn 1.5 O4、LiCr 0.3 Mn 1.7 O4、Li 1.1 Al 0.1 Mn 1.9 O4, Li2Mn2O4 and Li 1.5 One or more of Mn2O4.

[0166] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, aluminum foil or an aluminum alloy foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include a combination of one or more selected from aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. The polymer material base layer may include a combination of one or more selected from polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS) and polyethylene (PE).

[0167] In some embodiments, the positive electrode active material layer may further optionally include a positive electrode conductive agent. This application does not particularly limit the type of positive electrode conductive agent. For example, the positive electrode conductive agent may include a combination of one or more selected from superconducting carbon, conductive carbon black, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. In some embodiments, the mass percentage of the positive electrode conductive agent is less than 5% based on the total mass of the positive electrode active material layer.

[0168] In some embodiments, the positive electrode active material layer may further optionally include a positive electrode binder. The present application does not particularly limit the type of positive electrode binder. As an example, the positive electrode binder may include a combination of one or more selected from polyvinylidene fluoride (PVDF). In some embodiments, based on the total mass of the positive electrode active material layer, the mass percentage of the positive electrode binder is less than 5%. The crystallinity of the positive electrode binder is higher than that of the polymer described above in this application, and the melting temperature of the positive electrode binder is higher than that of the polymer described above in this application.

[0169] The positive electrode active material layer is typically formed by coating a positive electrode slurry onto a positive electrode current collector, drying, and cold pressing. The positive electrode slurry is typically formed by dispersing the positive electrode active material, the polymer, an optional conductive agent, an optional positive electrode binder, and any other components in a solvent and stirring them uniformly. The solvent may be, but is not limited to, N-methylpyrrolidone (NMP).

[0170] [Negative electrode]

[0171] The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode active material layer includes a negative electrode active material and a polymer. In the present application, the polymer includes the polymer described above.

[0172] For example, the negative electrode current collector has two surfaces facing each other in its thickness direction, and the negative electrode active material layer is provided on either or both of the two facing surfaces of the negative electrode current collector.

[0173] In some embodiments, 3.00<v / λ<50.00; alternatively, 3.40≤v / λ≤30.00. For example, v / λ can be 3.20, 3.40, 3.50, 4.00, 4.50, 5.00, 5.50, 6.00, 6.50, 7.00, 8.00, 9.00, 9.50, 10.00, 10.50, 11.00, 12.00, 13.00, 14.00, or a range consisting of any two of the above values.

[0174] In some embodiments, the polymer has a mass percentage of B% based on the mass of the negative electrode active material layer, wherein 0.2 ≤ B ≤ 5.0. When the polymer mass percentage is within the above range, the liquid absorption capacity of the negative electrode active material layer can be significantly improved. For example, the polymer mass percentage B% can be 0.2%, 0.5%, 0.8%, 1.0%, 1.2%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%, or a range consisting of any two of the above values.

[0175] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer base layer and a metal layer formed on at least one surface of the polymer base material. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy, etc.) on a polymer base material (such as a base material of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0176] In some embodiments, the negative electrode active material may adopt a negative electrode active material for a battery that is well known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate. The silicon-based material may be selected from at least one of elemental silicon, silicon oxides, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxides, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.

[0177] In some embodiments, the negative electrode active material layer may further include a negative electrode binder. The negative electrode binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS). The negative electrode binder may have a higher crystallinity than the polymers described above in this application, and a higher melting temperature than the polymers described above in this application.

[0178] In some embodiments, the negative electrode active material layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0179] In some embodiments, the negative electrode active material layer may further optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0180] In some embodiments, the negative electrode sheet can be prepared by the following method: the components for preparing the negative electrode sheet, such as the negative electrode active material, the polymer, the conductive agent, the negative electrode binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.

[0181] battery cells

[0182] In a second aspect, the present application provides a battery cell, comprising a positive electrode sheet, a negative electrode sheet, a separator disposed between the positive electrode sheet and the negative electrode sheet, and an electrolyte. The battery cell may be a lithium-ion battery, for example.

[0183] In some embodiments, the positive electrode plate may be any of the positive electrode plates of the first aspect of the present application, thereby improving the cycle performance of the battery cell. The negative electrode plate may be a conventional plate.

[0184] In some embodiments, the negative electrode plate may be any of the negative electrode plates of the first aspect of the present application, thereby improving the cycle performance of the battery cell. The positive electrode plate may be a conventional plate.

[0185] In some embodiments, the positive electrode plate can adopt the positive electrode plate of any embodiment of the first aspect of the present application, and the negative electrode plate can adopt the negative electrode plate of any embodiment of the first aspect of the present application, thereby improving the cycle performance of the battery cell.

[0186] [Electrolytes]

[0187] Battery cells also include an electrolyte, which conducts ions between the positive and negative electrodes. This application does not specify the type of electrolyte; it can be selected based on needs. For example, the electrolyte can be liquid, gel, or solid.

[0188] In some embodiments, the electrolyte is an electrolyte solution comprising an electrolyte salt and a solvent.

[0189] As an example, the lithium salt may include a combination of one or more selected from lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobis(oxalatophosphate) (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).

[0190] As an example, the organic solvent may include a combination of one or more selected from ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE).

[0191] In some embodiments, the electrolyte may further include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, and additives that improve battery high or low temperature performance.

[0192] [Isolation film]

[0193] In some embodiments, the battery cell further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical and mechanical stability can be selected.

[0194] In some embodiments, the material of the separator can include a combination of one or more of glass fiber, non-woven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film. When the separator is a multi-layer composite film, the materials of each layer can be the same or different.

[0195] In some embodiments, the positive electrode sheet, the separator, and the negative electrode sheet may be formed into an electrode assembly by a winding process or a lamination process.

[0196] The present application has no particular limitation on the shape of the battery cell, which can be cylindrical, square or any other shape. FIG1 shows a battery cell 5 with a square structure as an example.

[0197] In some embodiments, as shown in Figures 1 and 2, the outer packaging may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 is used to cover the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can be formed into an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is impregnated in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in the battery cell 5 can be one or more, which can be adjusted according to demand.

[0198] The manufacturing method of the battery cell of the present application is well known. In some embodiments, a positive electrode sheet, a separator, a negative electrode sheet, and an electrolyte can be assembled to form a battery cell. As an example, the positive electrode sheet, separator, and negative electrode sheet can be wound or laminated to form an electrode assembly. The electrode assembly is then placed in an outer packaging, dried, and then injected with electrolyte. The battery cell is then vacuum packaged, allowed to stand, formed, and shaped to obtain a battery cell.

[0199] In some embodiments of the present application, the battery cells according to the present application can be assembled into a battery module. The battery module can contain multiple battery cells, and the specific number can be adjusted according to the application and capacity of the battery module.

[0200] Figure 3 is a schematic diagram of an exemplary battery module 4. As shown in Figure 3 , within the battery module 4, multiple battery cells 5 may be arranged sequentially along the length of the battery module 4. Of course, any other arrangement is also possible. Furthermore, the multiple battery cells 5 may be secured together using fasteners.

[0201] Optionally, the battery module 4 may further include a housing having an accommodation space, and the plurality of battery cells 5 are accommodated in the accommodation space.

[0202] In some embodiments, the battery modules described above may also be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.

[0203] Figures 4 and 5 are schematic diagrams of an exemplary battery pack 1. As shown in Figures 4 and 5, the battery pack 1 may include a battery box and multiple battery modules 4 disposed within the battery box. The battery box comprises an upper case 2 and a lower case 3. The upper case 2 covers the lower case 3 and forms an enclosed space for accommodating the battery modules 4. The multiple battery modules 4 can be arranged in any manner within the battery box.

[0204] Both battery modules and battery packs can be used as examples of batteries in this application.

[0205] Electrical devices

[0206] In a third aspect, the present application provides an electrical device, which includes at least one of the battery cells, battery modules, and battery packs of the present application. The battery cells, battery modules, and battery packs can be used as power sources for the electrical device, or as energy storage units for the electrical device. The electrical device can be, but is not limited to, a mobile device (such as a mobile phone, a laptop computer, etc.), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship, a satellite, an energy storage system, etc.

[0207] The electric device can select a battery cell, battery module or battery pack according to its usage requirements. Figure 6 is a schematic diagram of an electric device as an example. The electric device 6 is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the high power and high energy density requirements of the electric device, a battery pack 1 or a battery module can be used. As another example, the electric device can be a mobile phone, a tablet computer, a laptop computer, etc. The electric device usually requires to be lightweight and thin, and a battery cell can be used as a power source.

[0208] Example

[0209] Below, the embodiment of the present application is described. The embodiment described below is exemplary, is only used to explain the present application, and is not to be construed as limiting the present application. Where specific techniques or conditions are not specified in the embodiment, the techniques or conditions described in the literature in this area or the product specifications are used. Reagents or instruments used that do not specify the manufacturer are conventional products that can be obtained commercially.

[0210] Example 1

[0211] (1) Preparation of positive electrode sheet:

[0212] Aluminum foil with a thickness of 12 μm was used as the positive electrode current collector.

[0213] A positive electrode slurry is prepared by mixing a fluorinated polymer, the positive electrode active material LiFePO4, the conductive agent carbon black, the binder polyvinylidene fluoride (PVDF), and N-methylpyrrolidone (NMP). The mass ratio of fluorinated polymer, LiFePO4, conductive carbon black, PVDF, and N-methylpyrrolidone (NMP) in the positive electrode slurry is 0.5:96.8:2:0.7:29. The positive electrode slurry is coated on a current collector aluminum foil and dried at 85°C before cold pressing. The sheet is then trimmed, cut, and slit, and then dried under vacuum at 85°C for 4 hours to form the positive electrode sheet.

[0214] (2) Preparation of negative electrode sheet:

[0215] A copper foil with a thickness of 8 μm was used as the negative electrode current collector.

[0216] Fluorinated polymer, artificial graphite (negative electrode active material), carbon black (conductive agent), styrene-butadiene rubber (SBR) (binder), sodium carboxymethyl cellulose (CMC) (thickener), and deionized water were mixed uniformly in a weight ratio of 2.5:94:0.5:2:1:100 to prepare the negative electrode slurry. The negative electrode slurry was coated on the current collector copper foil and dried at 85°C. After cold pressing, trimming, cutting, and slitting, the negative electrode sheet was dried at 120°C under vacuum for 12 hours.

[0217] (3) Preparation of electrolyte

[0218] In an environment with a water content of less than 10ppm, the non-aqueous organic solvents ethylene carbonate EC and ethyl methyl carbonate (EMC) are mixed in a volume ratio of 3:7 to obtain an electrolyte solvent. Subsequently, the lithium salt LiPF6 and the mixed solvent are mixed to prepare an electrolyte with a lithium salt concentration of 1 mol / L.

[0219] (4) Preparation of lithium-ion batteries:

[0220] A 16μm polyethylene film (PE) is used as a separator. The positive electrode sheet, separator, and negative electrode sheet are stacked in order, with the separator positioned between the positive and negative electrodes to provide insulation. The electrodes are then wound to form an electrode assembly. The electrode assembly is placed in an outer packaging shell, dried, and then injected with electrolyte. The battery undergoes vacuum packaging, resting, formation, and shaping to produce a lithium-ion battery.

[0221] Comparative Example 1

[0222] A lithium-ion battery was prepared using a method similar to that of Example 1. The difference from Example 1 was that a binder polyvinylidene fluoride (PVDF, crystallinity 48%, melting point 164°C) was added to the positive electrode plate of Comparative Example 1, and no other fluorinated polymer was added; a binder styrene-butadiene rubber was added to the negative electrode plate of Comparative Example 1, and no fluorinated polymer was added.

[0223] Comparative Example 2

[0224] A lithium-ion battery was prepared using a method similar to that of Example 1. The difference from Example 1 was that the positive electrode and the negative electrode of Comparative Example 2 were made of a fluorinated polymer.

[0225] Example 2 to Example 4

[0226] Lithium-ion batteries were prepared using a method similar to that of Example 1. The difference from Example 1 was that the positive and negative electrode sheets of Examples 2 to 4 were made of fluorinated polymers.

[0227] Example 5 to Example 7

[0228] Lithium-ion batteries were prepared using a method similar to that of Example 1. Unlike Example 1, the content of the fluorinated polymer in the positive electrode sheets of Examples 5 to 7 was adjusted.

[0229] Example 8 to Example 10

[0230] Lithium-ion batteries were prepared using a method similar to that of Example 1. The difference from Example 1 was that the content of the fluorinated polymer in the negative electrode sheets of Examples 8 to 10 was adjusted.

[0231] The data of the examples and comparative examples are shown in Table 1.

[0232] Test section

[0233] 1. Lithium-ion battery capacity retention test

[0234] The lithium-ion batteries prepared in the Examples and Comparative Examples were charged at room temperature at a constant current of 1C to 4.25V, then charged at a constant voltage of 4.25V to a current of 0.05C, left for 5 minutes, and then discharged at 1C to 2.8V. The resulting capacity was recorded as the initial capacity C0. Repeat these steps for the same battery, and simultaneously record the discharge capacity Cn of the battery after the nth cycle. The battery capacity retention rate after each cycle is Pn = Cn / C0 * 100%. A dot plot of the battery capacity retention rate versus the number of cycles is generated, with the 1200 points P1, P2, ..., P1200 as the ordinate and the corresponding number of cycles as the abscissa.

[0235] During this test, the first cycle corresponds to n=1, the second cycle corresponds to n=2, and so on, and the 1200th cycle corresponds to n=1200. For example, the battery capacity retention data corresponding to Example 1 in Table 1 is the data measured after 1200 cycles under the above test conditions, namely the value of P1200. The testing process for Comparative Example 1 and other examples is the same as above.

[0236] 2. Lithium-ion battery DC impedance test

[0237] The lithium-ion batteries prepared in the Examples and Comparative Examples were charged at 1 / 3C constant current to 4.25V at 25°C, then charged at 4.25V constant voltage to a current of 0.05C. After 5 minutes of rest, the voltage V1 was recorded. The batteries were then discharged at 1 / 3C for 30 seconds, and the voltage V2 was recorded. The internal resistance DCR1 of the battery after the first cycle was calculated as (V2-V1) / 1 / 3C. The above steps were repeated for the same battery, and the internal resistance DCRn of the battery after the nth cycle (n=1, 2, 3, ..., 1200) was simultaneously recorded. The 1200 points (DCR1, DCR2, DCR3, ..., DCR1200) were plotted as the ordinate, and the corresponding cycle number as the abscissa, to produce a graph of the battery discharge DCIR versus cycle number for the polymers in the Examples and Comparative Examples.

[0238] During this test, the first cycle corresponds to n=1, the second cycle corresponds to n=2, and so on, and the 1200th cycle corresponds to n=1200. For example, the internal resistance increase ratio of the battery in Example 1 in Table 1 = (DCRn - DCR1) / DCR1 * 100%. The testing procedures for Comparative Example 1 and the other examples are the same as above. The data in Table 1 were measured after 1200 cycles under the above test conditions.

[0239] Test results

[0240] Table 1

[0241]

[0242] In Table 1, VDF represents vinylidene fluoride, HFP represents hexafluoropropylene, and TFE represents tetrafluoroethylene. 90% VDF means that the molar percentage of VDF is 90% based on the total molar amount of VDF and HFP, and 10% FEP means that the molar percentage of FEP is 10%.

[0243] As can be seen from Table 1, compared with Comparative Example 1, the embodiment of the present application adds the fluorinated polymer of the present application to the positive electrode sheet and / or the negative electrode sheet. The fluorinated polymer can form uniform high wetting points inside the active material layer, uniformly improve the wetting performance of the active material layer, thereby improving the overall liquid absorption speed of the active material layer, thereby improving the cycle performance of the battery cell using the electrode sheet.

[0244] Compared with Comparative Example 2, the embodiment of the present application can more significantly improve the cycle performance of the lithium-ion battery when v / λ>1 is satisfied.

[0245] Although the present application has been described with reference to preferred embodiments, various modifications may be made thereto and components may be substituted with equivalents without departing from the scope of the present application. In particular, the various technical features described in the various embodiments may be combined in any manner as long as there are no structural conflicts. The present application is not limited to the specific embodiments disclosed herein, but encompasses all technical solutions within the scope of the claims.

Claims

1. A pole piece, comprising a current collector and an active material layer disposed on at least one surface of the current collector, wherein the active material layer comprises an active material and a polymer, and the active material layer satisfies: v / λ>1.00 Formula (3); In formula (1) to formula (3), λ represents the porosity of the active material layer; P1 represents the actual compaction density of the active material layer, and its unit is g / cm 3 ; P2 represents the actual compacted density of the active material, in g / cm 3 ; v represents the liquid absorption rate of the active material layer, and its unit is mg / s; d represents the diameter of the capillary of the active material layer in the capillary test, and its unit is mm; h represents the height of the liquid level in the capillary tube, and its unit is mm; ρ represents the density of the electrolyte in the capillary test, and its unit is g / cm 3 ; t represents the time for the electrolyte to be absorbed in the capillary, and its unit is s.

2. The pole piece according to claim 1, wherein: The active material includes a positive electrode active material, and the active material layer satisfies: 1.00<v / λ<4.00; optionally, 1.20≤v / λ≤3.

80.

3. The pole piece according to claim 1 or 2, wherein: The active material includes a positive electrode active material, and based on the mass of the active material layer, the mass percentage of the polymer is A%; Among them, 0.1≤A≤1.

5.

4. The pole piece according to claim 1, wherein: The active material includes a negative electrode active material, and the active material layer satisfies: 3.00<v / λ<50.00; optionally, 3.40≤v / λ≤30.

00.

5. The pole piece according to claim 1 or 4, wherein: The active material includes a negative electrode active material, and based on the mass of the active material layer, the mass percentage of the polymer is B%; Among them, 0.2≤B≤5.

0.

6. The pole piece according to any one of claims 1 to 5, wherein: The crystallinity of the polymer measured by differential scanning calorimetry is X C %,0<X C ≤30; The melting temperature of the polymer is Tm, the unit is °C, 0<Tm≤140.

7. The pole piece according to any one of claims 1 to 6, wherein: The glass transition temperature of the polymer is Tg, the unit of which is °C, -150≤Tg≤60.

8. The pole piece according to any one of claims 1 to 7, wherein: The polymer comprises at least one of the structural units represented by formula (I) to the structural units represented by formula (III), In formula (I) and formula (II), R1, R2, R3 and R4 each independently include a hydrogen atom, a fluorine atom, a chlorine atom, a substituted or unsubstituted C1-C3 alkyl group or a substituted or unsubstituted C1-C3 alkoxy group, and at least one of R1, R2, R3 and R4 includes a fluorine atom; when substituted, the substituent includes a fluorine atom; Optionally, R1, R2, R3 and R4 each independently include a hydrogen atom, a fluorine atom, a chlorine atom, a substituted or unsubstituted C1-C2 alkyl group or a substituted or unsubstituted C1-C2 alkoxy group; further optionally, R1, R2, R3 and R4 each independently include a hydrogen atom, a fluorine atom, a chlorine atom, a methyl group, a fluoromethyl group, a methoxy group or a perfluoromethoxy group; In formula (III), R5 includes a single bond, a substituted or unsubstituted C1-C3 alkyl group; when substituted, the substituent includes a fluorine atom; p is a positive integer selected from 1 to 3; n is a positive integer selected from 1,000 to 30,000.

9. The pole piece according to any one of claims 1 to 8, wherein: The polymer includes at least one of the structural units represented by formula (I-1) to the structural units represented by formula (I-11), 10. The pole piece according to any one of claims 1 to 9, wherein: The polymer further comprises at least one of the structural units represented by formula (II-1) to the structural units represented by formula (II-5), 11. The pole piece according to any one of claims 1 to 10, wherein: The polymer further comprises at least one of the structural units represented by formula (III-1) to the structural units represented by formula (III-3), 12. The pole piece according to any one of claims 8 to 11, wherein: n is a positive integer selected from 5000 to 20000; and / or The molecular weight of the polymer is 2×10 5 g / mol to 1.5×10 6 g / mol.

13. A battery cell comprising the pole piece according to any one of claims 1 to 12.

14. A battery comprising the battery cell according to claim 13.

15. An electrical device comprising the battery according to claim 14.

Citation Information

Patent Citations

  • Fluorine-containing polymer, preparation method and application thereof, binder composition, secondary battery, battery module, battery pack and electric device

    CN115124638A